PENERAPAN PEMBELAJARAN INTERAKTIF MENGGUNAKAN BAHAN AJAR POWERPOINT BEREFEKTIF PADA PEMBELAJARAN IPA DI SEKOLAH DASAR KELAS RENDAH - Wahyuni, Riris; Witarsa, Ramdhan (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2023)
Good teaching materials are needed to be applied to natural science learning in elementary schools. Teaching materials must be able to accommodate the needs of low-grade students so that students can interact better during learning. This research was conducted with the aim of producing interactive learning patterns using powerpoint media in natural science learning for low-grade elementary school students. This research was conducted using a qualitative research method. This method has four stages, namely data collection, data reduction, data processing, and conclusion. The respondents were elementary school students in the lower grades (grades 2 and 3). The results showed that powerpoint teaching materials have high effectiveness in interactive learning in the process of learning natural science in low grade elementary schools. Elementary school teachers should use powerpoint teaching materials more often so that natural science learning can be more effective in producing complete student learning outcomes, both cognitively, affectively and psychomotorically.